Replicating Local Good Practices in Regulating the Business Environment at the National Level : What Italy’s Experience Reveals - Bettarelli, Luca; Rooms, Tommaso (World Bank, Washington, DC, 2022)
Excessive bureaucracy at any time is a burden on companies. In the context of the recovery from the COVID-19 crisis, it is an additional hurdle that jeopardizes the ability of small and medium enterprises to survive. Using the example of Italy, and drawing on primary data from the World Bank’s Subnational Doing Business studies, this brief highlights how identifying local good practices in regulating the business environment and promoting them to national standards is one of the most powerful tools policy makers have to sustain firms’ creation and growth, reduce spatial inequality, and help create economic opportunities.